1999
DOI: 10.1038/46303
|View full text |Cite
|
Sign up to set email alerts
|

Activated T cells regulate bone loss and joint destruction in adjuvant arthritis through osteoprotegerin ligand

Abstract: Bone remodelling and bone loss are controlled by a balance between the tumour necrosis factor family molecule osteoprotegerin ligand (OPGL) and its decoy receptor osteoprotegerin (OPG). In addition, OPGL regulates lymph node organogenesis, lymphocyte development and interactions between T cells and dendritic cells in the immune system. The OPGL receptor, RANK, is expressed on chondrocytes, osteoclast precursors and mature osteoclasts. OPGL expression in T cells is induced by antigen receptor engagement, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,061
1
36

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,683 publications
(1,133 citation statements)
references
References 22 publications
35
1,061
1
36
Order By: Relevance
“…The finding of increased T cell activation and proliferation in mice with T cell-specific blockade of TGF␤ signaling is consistent with both the augmented Ag presentation observed in these transgenic mice and the direct repressive action of TGF␤ on T cell proliferation and differentiation. An expected consequence of increased T cell activation is increased production of osteoclastogenic cytokines (12,32,33). Measurements by ELISA of cytokine levels in 72-h culture media revealed that T cells derived from CD4dnTGF␤IIR mice produce significantly higher levels of TNF (Fig.…”
Section: Tgf␤ Represses T Cell Activation and Proliferation In E-replmentioning
confidence: 99%
“…The finding of increased T cell activation and proliferation in mice with T cell-specific blockade of TGF␤ signaling is consistent with both the augmented Ag presentation observed in these transgenic mice and the direct repressive action of TGF␤ on T cell proliferation and differentiation. An expected consequence of increased T cell activation is increased production of osteoclastogenic cytokines (12,32,33). Measurements by ELISA of cytokine levels in 72-h culture media revealed that T cells derived from CD4dnTGF␤IIR mice produce significantly higher levels of TNF (Fig.…”
Section: Tgf␤ Represses T Cell Activation and Proliferation In E-replmentioning
confidence: 99%
“…Additionally, although cytokines that contribute to osteoclast differentiation during inflammation, such as TNF␣ and interleukin 1, can activate NF-B and AP-1 (13,14) in osteoclast precursor cells, RANK and RANKL remain essential for osteoclastogenesis in vivo. For instance, administering osteoprotegerin to rats with adjuvant-induced arthritis abrogates osteoclastogenesis and subsequent bone loss without inhibiting inflammation (15). Furthermore, bone erosion induced by overexpression of TNF␣ in transgenic mice can be alleviated by administering RANK-Fc or by crossing TNF␣ transgenic mice into a RANK-null background (16).…”
mentioning
confidence: 97%
“…M-CSF and RANK ligand (RANKL) have been shown to be critical factors for the differentiation of OCL, which are physiologically produced by stromal cells and osteoblasts (Lacey et al, 1998). Kong et al (1999) identified abnormal expression of RANKL on activated T lymphocytes and postulated that this gene is associated with bone loss and joint destruction in inflammatory arthritis. Among the genes associated with hypercalcemia, increased expression of the RANKL gene correlated with hypercalcemia in ATL.…”
Section: Rank Ligandmentioning
confidence: 99%